Learning in the age of algorithmic cultures. (May 2017) - Jandrić, Petar; Knox, Jeremy; Macleod, Hamish; Sinclair, Christine
This Editorial describes the main challenges at the intersections between algorithmic cultures and human learning. It briefly analyses papers in this Special Issue of E-learning and Digital Media 'Learning in the age of algorithmic cultures' and shows that researchers in the field are still struggling with grand ideas and questions. It suggests that studies of algorithms and learning are in their infancy and emphasizes that they carry potentials to confirm our existing ideas and surprise us with fresh insights.